Precipitation of rhodium from a copper sulphate leach solution in the selenium/tellurium removal section of a base metal refinery - Lottering, C.; Eksteen, Jacques; Steenekamp, N. (SAIMM, 2012)
Copper sulphate solutions are produced during the pressure leaching of first-stage leach residue in a typical base metal refinery process. Apart from impurities such as selenium and tellurium, this leach solution also contains other precious metals (Rh, Ru, and Ir) due to dissolution in the pressure leaching stage. Selenium and tellurium are removed from the leach solution by precipitation with sulphurous acid, since these elements negatively affect electrowinning. This study investigates the feasibility of modifying the Se/Te precipitation process step to achieve significant rhodium precipitation in addition to selenium and tellurium precipitation, in order to reduce the rhodium inventory of the process. Thiourea, SO2, formaldehyde, formic acid, and sodium thiosulphate were evaluated to determine which of these reagents would achieve the highest Rh precipitation. Based on these screening tests, SO2 and thiourea were selected to be used as precipitation reagents in optimization tests. During these optimization tests, the operating temperature (80 to 150°C) and the amount of reagent added (80 to 140 per cent excess) were varied to evaluate the effects that these operating conditions have on the precipitation behaviour of Rh as well as Se, Te, Cu, and Ni, and to propose appropriate operating conditions. It was found that thiourea resulted in good Rh and Se precipitation (typically in excess of 90 per cent), but precipitated noticeably more copper and nickel from the solution than when SO2 was used. In addition, thiourea had poor Te removal characteristics. SO2 achieved a maximum of 70 per cent precipitation of the rhodium. Faster kinetics and a larger extent of Te precipitation were, however, observed when using SO2 compared to thiourea.